Australian Wool Innovation everything you need to know about Australian Merino wool - Australian Wool Innovation (Firm) (Sydney : Australian Wool Innovation Pty Ltd, 2001)
World Wide Web site of Australian Wool Innovation Limited, containing information on the organisation, its campaigns, copies of reports, news and audio files in English and some of them in Chinese version site.
Title from title screen (viewed on 8 Oct. 2001).
Text and graphics.
Mode of access: Internet via World Wide Web. Available at: http://www.wool.com.au
Site in English and Chinese.
Selected for archiving
Keywords: Wool industry -- Australia